PENGARUH MOTIVASI ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Saputri, Eva; Aminuyati, Aminuyati; BU, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether there is an influence of parents' motivation on the learning outcomes of students of economic subjects in class XI IPS 4 at MAN 1 Pontianak. Descriptive research method with the form of relationship research studies. The population of students in class XI IPS 4, amounting to 35 people, using saturated samples totaling 35 students of class XI IPS 4 in MAN 1 Pontianak. Technique of collecting indirect communication techniques and documentary study techniques. Data collection tools used were questionnaires / questionnaires and documentation. The results showed that there was a positive and significant relationship between the independent variable (X) and the dependent variable (Y) or student learning outcomes with a large correlation value or R relationship that was equal to 0.572 moderate categories. The data analysis technique is based on the equation 10.325 + 0.651X. The results of the t test show that tcount> t table is (4.001> 2,035). So Ha is accepted and Ho is rejected. Thus it can be said that there is an influence of parents' motivation on the learning outcomes of students of economic subjects in class XI IPS 4 at MAN 1 Pontianak. The results of the coefficient of determination (R2) amounted to 0.327 which means the percentage of contribution of influence was 32.7%, while the remaining 67.3% was influenced by other factors such as interests and rivals / competition which were not examined in this study.Keywords:Parental Motivation, Student Learning OutcomesÂ